Two-Port Needle-Assisted Pediatric Laparoscopic Herniotomy Using Tuohy Needle: Clinical Experience and Outcomes - Imran Abbas; Rida Fatima; Muhammad Aslam Javed; Muhammad Hassan; Mahmood Farooqi; Muhammad Mohsin Gillani (Pakistan Journal of Medicine and Dentistry)
Background: Traditionally, inguinal hernia in the pediatric population is managed with open herniotomy; the procedure has evolved significantly with the advancement of minimally invasive laparoscopic techniques. Tuohy Needle-assisted Laparoscopic hernia repair has several advantages over the open repair technique, including shorter recovery times, the ability to evaluate and repair contralateral defects, reduced postoperative complications, and improved outcomes.